Supplementary Table 4: SpatialDecon derived immune cell counts from Spatially Resolved Transcriptomics Deconvolutes Prognostic Histological Subgroups in Patients with Colorectal Cancer and Synchronous Liver Metastases - Colin S. Wood (15293247) (2025)
SpatialDecon derived immune cell counts aggregated by Region, KM grade and KRAS status with pairwise comparison between groups. Mann-Whitney test used to determine statistical significance between groups